2015
DOI: 10.1016/j.jphotochem.2015.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chloro substituent on photoisomerization, redox reactions and water oxidation catalysis of mononuclear ruthenium complexes

Abstract: distal-[Ru(Cl-tpy)(pynp)Cl] + (d-2Cl) (Cl-tpy = 4'-chloro-2,2';6',2"-terpyridine, pynp = 2-(2-pyridyl)-1,8-naphthyridine), and distaland proximal-[Ru(Cl-tpy)(pynp)OH 2 ] 2+ (d-and p-2H 2 O) complexes are newly synthesized and characterized to compare structures and physicochemical properties with a 2,2';6',2"-terpyridine (tpy) ligand derivatives of distal-[Ru(tpy)(pynp)Cl] + (d-1Cl), distal-and proximal-[Ru(tpy)(pynp)OH 2 ] 2+ (d-and p-1H 2 O). The equilibrium turned out to be involved in the aquation reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(54 citation statements)
references
References 44 publications
6
46
2
Order By: Relevance
“…We recently reported irreversible [35][36][37][38] and reversible photoisomerizations [39] of mononuclear ruthenium aqua complexes havinga na symmetric bidentate ligand (Scheme 1). The reversibilityo ft he reactioni sc ontrolled by intramolecular hydrogen bondingb etween the aqua ligand and the pendant moiety of the bidentate ligand.…”
mentioning
confidence: 99%
“…We recently reported irreversible [35][36][37][38] and reversible photoisomerizations [39] of mononuclear ruthenium aqua complexes havinga na symmetric bidentate ligand (Scheme 1). The reversibilityo ft he reactioni sc ontrolled by intramolecular hydrogen bondingb etween the aqua ligand and the pendant moiety of the bidentate ligand.…”
mentioning
confidence: 99%
“…When an aqueous solution of d-Cl1 was irradiated with visible light (λ > 420 nm, 180 mWcm À2 ), the stoichiometric photoisomerization of d-Cl1 to p-Cl1 was observed as it is for d-1 (Figure 1). The rate constant for photoisomerization of d-Cl1 was estimated to be (k d-p ) obs = 4.9 x 10 À3 s À1 [35], which is higher than that ((k d-p ) obs = 4.1 x 10 À3 s À1 ) [22,34] observed for d-1 under the same conditions (Table 1). Additionally, the Φ value of d-Cl1 (2.1%) is higher than that (Φ =1.5%) of d- 1. Several groups reported that some polypyridyl complexes undergo photosubstitution reactions via the triplet metal centered ( 3 MC) state from the 3 MLCT excited state [25][26][27].…”
Section: Irreversible Photoisomerization Of Distal-[ru(xtpy)(pynp)oh 2 ] 2+ To the Proximal-isomermentioning
confidence: 67%
“…The chemical water oxidation catalyzed by d-1Cl and p-1Cl was investigated under the same conditions as the dÀ/p-1 isomer system to understand the effect of 4 0 -chloro-substitusion on tpy ligand on the catalytic activity of the distalÀ/proximal-isomer complexes for water oxidation [35]. v O2 increased linearly with respect to the complex amount for d-1Cl and p-1Cl, as is the case of the dÀ/p-1 isomer system (Figure 18).…”
Section: Comparison In Catalytic Activities Between Distal and Proximal Isomers Of Mononuclear Ruthenium Complexesmentioning
confidence: 99%
See 2 more Smart Citations